LANGUAGE USE, INTERACTIONS, AND SOCIAL DIMENSIONS: ARE THERE ANY CONSIDERATIONS TAKEN BY CHILDREN WHEN MAKING REQUESTS TO THEIR INTERLOCUTORS? - Rusminto, Nurlaksana Eko; Widodo, Mulyanto (Universitas Islam Sumatera Utara (UISU), 2022)
According to literature, a child’s request is always addressed to a specific person or group of people. To our knowledge, however, studies on language use, interactions, and social dimensions in relation to request making to an interlocutor are uncommon in the Indonesian context; therefore, we sought to describe the considerations taken by children when making requests. Forty children between the ages of 6 and 10 took part in this qualitative study. We collected data using observation and field notes. The collected data were subsequently analyzed using an interactive model. The findings indicate that the majority of children's requests are directed toward interlocutors who are classified as having an extremely close relationship. In contrast, children never make direct requests to interlocutors classified as quite distant or extremely distant. The findings also indicate that requests made to interlocutors with a higher social status than children use a particular verbal form based on the nature of the request and the implied context. In contrast to reality, requests made to interlocutors with a lower social status are more likely to be made directly. It is hoped that the findings of this study will contribute to pragmatic and speech-related theories, as well as to improvements in language education based on a communicative and contextual approach that returns language to its primary function as a tool for communication and places language learning in a meaningful context.